1987
DOI: 10.1002/j.1556-6978.1987.tb00730.x
|View full text |Cite
|
Sign up to set email alerts
|

Reference Inaccuracies in Two Counseling Journals

Abstract: Article, book, and dissertation entries in reference lists in one volume year for two counseling journals were searched for accuracy. Among 2,388 verified references (85.7% of all cited references), 1,072 (44.9%) contained at least one error. Multiple errors in some references produced a total of 1,643 faults or errors. Data were tallied by reference segments (e.g., author, title). Findings paralleled data in five reports of similar research, principally for medical journals, published in the 1970s. The nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…A search of social work literature has revealed that this is the only study of reference list accuracy in this field. Other fields, however, appear to acknowledge the importance of reference accuracy through a rich knowledge base in their respective bodies of literature, including medicine (De Lacey, Record & Wade, 1985;Evans, Nadjari & Burchell, 1990), nursing (Taylor, 1998), and psychology (Faunce & Job, 2001;White, 1987).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A search of social work literature has revealed that this is the only study of reference list accuracy in this field. Other fields, however, appear to acknowledge the importance of reference accuracy through a rich knowledge base in their respective bodies of literature, including medicine (De Lacey, Record & Wade, 1985;Evans, Nadjari & Burchell, 1990), nursing (Taylor, 1998), and psychology (Faunce & Job, 2001;White, 1987).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The present study was conducted in response to concerns that arose from consideration of several studies on reference inaccuracies, most notably Goodrich and Roland (1977), Hartmann (1984), Key and Roland (1977), and Poyer (1979), in addition to several of the studies cited above. White (1986aWhite ( , 1986bWhite ( , 1987aWhite ( , 1987bWhite ( , 1987c also found an alarmingly high average error rate of approximately 40% both across journals and across time. If errors occurred in the references at such a high rate and with such consistency, how accurate were the direct quotations appearing in those journals?…”
mentioning
confidence: 94%
“…The reference list and the reference citations in the text must match, and the references themselves must be correct. White (1987) found that over 40% of the references in just two refereed national journals contained inaccurate information, and as Martin Ritchie (1995), editor of Counselor Education and Supervision, wrote, "Insufficient or inaccurate literature reviews not only detract from the article, they can make it unpublishable" @. 3).…”
mentioning
confidence: 99%